Experts in Times of Pandemic: Reframing the Debate in the Context of Structural Transformations of the Public Sphere - Verovšek, Peter J.; Gorišek, Maruša (Javnost-The Public, 2023)
The Covid-19 pandemic has highlighted the important yet controversial role of scientific expertise in public life. While existing debates focus mostly on necessary changes to (1) how experts are involved in public and political debates or (2) the way science itself is conducted, we conceptualise role of digital technology and the rise of the “new” social media through the theoretical framework provided by Jürgen Habermas. Drawing on Habermas’s recent reflections on the new “structural transformation” of the digital public sphere, we identify two areas where science and its interaction in the public sphere can be improved to address declining trust in scientific expertise: namely, digital design and user education. On the one hand, democracies need to focus on the architecture of the public sphere when trying to re-establish trust in science. On the other hand, individual user education addresses the choices individuals are making regarding which information they use when they engage in public debates.